2020
DOI: 10.1101/2020.07.06.187187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking Age Differences in Neural Distinctiveness across Representational Levels

Abstract: SummaryThe distinctiveness of neural information representation is crucial for successful memory performance but declines with advancing age. Computational models implicate age-related neural dedifferentiation on the level of item representations, but previous studies mostly focused on age differences of categorical information representation in higher-order visual regions. In an age-comparative fMRI study, we combined univariate analyses and whole-brain searchlight pattern sim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 77 publications
5
17
2
Order By: Relevance
“…Complementary evidence is accumulating from studies using multivariate approaches such as neural pattern analysis (Carp et al, 2011;Zheng et al, 2018). Accordingly, in a recent study (Kobelt et al, 2020) we observed age group differences in neural specificity during encoding not only on the level of category information, but even on the item-level, providing further evidence for the crucial contribution of specific, high-quality memories for memory performance. Strikingly, age differences on the item level were located in occipital regions, thus early in the visual processing hierarchy, in line with early observation of a close connection between age-differences in perception and cognition (Baltes & Lindenberger, 1997;Lindenberger & Baltes, 1994).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Complementary evidence is accumulating from studies using multivariate approaches such as neural pattern analysis (Carp et al, 2011;Zheng et al, 2018). Accordingly, in a recent study (Kobelt et al, 2020) we observed age group differences in neural specificity during encoding not only on the level of category information, but even on the item-level, providing further evidence for the crucial contribution of specific, high-quality memories for memory performance. Strikingly, age differences on the item level were located in occipital regions, thus early in the visual processing hierarchy, in line with early observation of a close connection between age-differences in perception and cognition (Baltes & Lindenberger, 1997;Lindenberger & Baltes, 1994).…”
Section: Discussionsupporting
confidence: 53%
“…Park et al, 2012;Voss et al, 2008). Importantly, interindividual differences in neural dedifferentation are related to memory performance (Kobelt et al, 2020;, such that participants with higher levels of neural dedifferentiation showed lower memory performance (for a recent review see . Complementary evidence is accumulating from studies using multivariate approaches such as neural pattern analysis (Carp et al, 2011;Zheng et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with this, it has been suggested that neural representations become less specific in old age, which may be linked to aging-related cognitive decline (Carp et al, 2011;Li and Sikström, 2002;Li et al, 2001;Park et al, 2004Park et al, , 2010. Indeed, a positive relation between the specificity of the neural activity patterns during encoding and memory performance could be demonstrated for young and older adults (Kobelt et al, 2020;Koen et al, 2019). In children (7-12 years), higher neural specificity of scene representations was associated with better memory performance, too (Fandakova et al, 2019).…”
Section: Introductionmentioning
confidence: 84%
“…The loss of mnemonic detail and reduced specificity of memory content in older adults is also reflected in age differences in the specificity of neural activation, so-called neural dedifferentiation (Bowman et al, 2019;Sommer et al, 2020; for review, see parahippocampal place area respectively), older adults show a decrease in this neural selectivity (Park et al, 2004). Recent studies using multivariate pattern analysis support this initial finding and underline the relevance of neural specificity for memory performance (Kobelt et al 2020;Zheng et al, 2018). Age differences in oscillatory mechanisms of memory formation (Werkle-Bergner et al, 2006) and retrieval may further contribute to the reduced memory specificity in older adults, but remarkably few studies have addressed this question as yet.…”
Section: Introductionmentioning
confidence: 89%